LAST MILE TRIPS: Logistics distribution infrastructure in smart cities and the experiences of service provision in the Metropolitan Region of Recife - PE - Queiroz, Alessandro Pelópidas Ferreira de; Guimarães Júnior, Djalma Silva (Revista Nacional de Gerenciamento de Cidades, 2022)
The present research aims to explore the main technologies added in the last mile logistics distribution infrastructure models used in smart cities, as well as relate them to the experiences of companies that provide these services in the Metropolitan Region of Recife (MRR). In order to do so, a case study is presented on the logistics distribution system used by a company that performs last mile delivery in the MRR. The data were collected through the application of a questionnaire to the manager of the company in question. Considering the studies analyzed on the subject, the implementation of new models of last mile logistics distribution in smart cities around the world, such as pick-up points, lockers, crowdsourcing and crowdshipping, was evident. Regarding the logistics distribution infrastructure used in the MRR, the results obtained showed that the application of the new models is still limited. It is concluded that the existence of public/private partnerships is essential for the introduction and strengthening of new last mile logistics distribution systems used in cities, whether they are considered smart or not.